Pharmacokinetic/Pharmacodynamic Modeling of Tulathromycin against Pasteurella multocida in a Porcine Tissue Cage Model - Zhou, Qiaoyi; Zhang, Guijun; Wang, Qin; Liu, Wenguang; Huang, Yan; Yu, Pengling; Li, Yanqin; Ding, Huanzhong; Fang, Binghu (Frontiers in Pharmacology, 2017)
Tulathromycin, a macrolide antibiotic, is used for the treatment of respiratory disease in cattle and swine. The aim of our study was to investigate the in vitro and ex vivo activities of tulathromycin in serum, (noninflamed) transudate, and (inflamed) exudate against Pasteurella multocida in piglets. The pharmacokinetics properties of tulathromycin were studied for serum, transudate, and exudate using a tissue cage model. In vitro antibiotic susceptibility of P. multocida and dynamic time-kill curve experiments over eight tulathromycin concentrations were determined. The ratio of 24-h area under the concentration–time curve to minimum inhibitory concentration (AUC(0-24h)/MIC) was recognized as an important pharmacokinetic/pharmacodynamic (PK/PD) parameter of tulathromycin for antibacterial efficiency (R2= 0.9969). In serum ex vivo, for bacteriostatic, bactericidal activity, and virtual bacterial eradication AUC(0-24h)/MIC values for tulathromycin were 44.55, 73.19, and 92.44 h by using sigmoid Emax model WinNonlin software, respectively, and lower values were obtained for exudate and transudate. In conjunction with the data on MIC90, the dose of tulathromycin for a bacteriostatic effect and virtual elimination of P. multocida as computed using the value of the PK/PD breakpoint obtained in serum were 6.39 and 13.25mg/kg. However, it would be preferable to calculate a dose combined with population pharmacokinetics data to optimize the dosage regimen for bacteriological and clinical cure.